Pengaruh Jumlah Wisatawan dan Obyek Wisata terhadap Produk Domestik Regional Bruto di Provinsi Jambi - Rika Nurmazeli (Universitas Batanghari Jambi, 2020)
This study aims to examine and analyze: 1) The effect of the number of tourists on gross regional domestic product in Jambi province in 2016-2018; 2) the effect of the number of attractions on gross regional domestic product in Jambi province in 2016-2018.This research is a data collection with documentation techniques sourced from the Central Statistics Agency (BPS), the data in this study are secondary data. The data used in the form of time series data and some 11 district / city objects (cross section). The data analysis tool used is panel data regression.The results of data analysis show that the number of tourists has a positive and not significant effect on gross regional domestic product in Jambi Province in 2016-2018; 2) Tourism Object has positive and not significant effect on gross regional domestic product in Jambi Province in 2016-2018